Regionalization and integration of the global economy - Kaliakparova, G.Sh.; Gridneva, Y.E.; Kalmanova, N.М. (BUKETOV BUSINESS REVIEW, 2020)
Object: The aim is to disclose the processes of involving most of humanity in a single system of financial, economic, socio-political and cultural ties, demanding effective ways to streamline relations in a space. Like other countries Kazakhstan is involved in the process of regionalization, Kazakhstan is also interested in free access to foreign markets. The authors of the article determined the role of Kazakhstan in the international community in matters of regionalization and integration. Methods: The main methods: analysis, detailing, generalization. Findings: It has been established that free economic zones, having a structural effect on the international movement of goods, services, capital, contribute to the processes of globalization and the development of economic integration. Conclusions: During the writing of the article, the authors concluded that regionalization and integration of the economy have both positive and negative sides. On the one hand, they contribute to the convergence of national economies that interact with each other. On the other hand, it is contributing to the split of a single world market, which is leading to rivalry and competition.